Translation of Data into Action: Exploring Data Documentation process and further Scope for Improvement in Bangladesh - Biswas, Animesh; Purno, Nabila Hossain; Doraiswamy, Sathyanarayanan (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study done to explore the data documentation process of fistula in the facilities and scope to improve. Methods: In-depth reviews of patents data recoding forms of six selected facilities were performed. Of them, three were government and remaining were private facilities. The study also explored the process of data documentation, reporting in the DHIS-2. Results: All centers are keeping records of fistula patients; five of them use structured forms. One government facility uses hospital register book to record the data. There was inconsistency in all six different forms. Therefore, uniform data is not captured. Rehabilitation data is missing in the data records. Government facilities report information on number of cases operated in the DHIS-2. While, private facilities are not under this reporting system. Thus, there are gaps identified in the documentation process and reporting system. Conclusions: Better data helps for better planning and intervene. Bangladesh is documenting gential fistula patient’s data. However, its demands for improvement. A comphesive and uniform database can help to eliminate fistula in Bangladesh as set target in the 2nd national strategy.